Is vitamin C enough? A case report of scurvy in a five-year-old girl and review of the literature - Timothy Hahn; Whitney Adams; Keith Williams (BMC, 2019)
Abstract Background Numerous cases of scurvy secondary to diet limitations have been reported in the literature with most being boys with special needs. To date, the focus of the literature describing vitamin C deficiency has been the medical sequelae of the deficiency. There has been little attention given underlying diet limitations causing the vitamin C deficiency. Case presentation A five-year-old female with typical development initially presented with rash, then later for pain in both lower extremities. After evaluation revealed vitamin C deficiency, she was admitted into an intensive day treatment feeding program. A feeding assessment found she had life-long problems with eating and had a diet that never exceeded ten foods. Across the course of treatment, she learned to eat 29 new foods. At six-month follow-up her body mass index had increased from the 1st to the 61st percentile. At one-year follow-up her body mass index was at the 85th percentile. All sequalae of her deficiency resolved. Conclusions This case is unusual as most reported studies describe males with special needs. The severity of her eating issues suggest providers may consider referral to allied health professionals to address diet limitations for both children identified with nutrient deficiencies as well as children whose selective eating places them at risk for nutritional deficiencies or problems with growth. The child we described was anemic, like 42% of children described in the case literature on scurvy and like 32% of the children in this literature, our patient was underweight. In the literature, comorbid nutrient deficiencies were reported in 22% of the scurvy case studies. We suggest vitamin C supplementation is a necessary component for addressing vitamin C deficiency, but insufficient for addressing the diet limitations causing the nutrient deficiency.